Subcostal closure technique for prevention of postthoracotomy pain syndrome. (September 2016) - Hong, Kipyo; Bae, Mikyung; Han, Sora
Background: The purpose of this study was to evaluate the efficacy of our subcostal closure technique in prevention of postthoracotomy pain syndrome. Methods: From July 2012 to March 2015, 29 patients in whom a lobectomy was indicated underwent a thoracotomy. The thoracotomy wounds were closed using a subcostal closure technique (subcostal closure group) and outcomes were compared with 31 patients who underwent video-assisted thoracoscopic surgery (thoracoscopy group). The duration of oral opioid consumption was evaluated from medical records, and postoperative pain was evaluated by telephone interview conducted by a trained nurse practitioner who was unaware of the patient's group. Results: Pain scores were higher in the thoracoscopy group compared to the subcostal closure group, reaching statistical significance (Numeric Rating Scale 0.55 ± 0.948 in the subcostal closure group vs. 1.84 ± 1.614 in the thoracoscopy group; p < 0.001, Clinical Pain Scale 0.24 ± 0.435 in the subcostal closure group vs. 0.81 ± 0.703 in the thoracoscopy group; p < 0.001). The number of patients who consumed oral opioids for longer than 2 months after the operation was significantly greater in the thoracoscopy group than the subcostal closure group (6.9% in the subcostal closure group vs. 32.3% in the thoracoscopy group; p = 0.022). Conclusions: The subcostal closure technique is useful to prevent postthoracotomy pain syndrome.